An Innovative Tour Recommendation System using Graph Algorithms - Md. Sabir Hossain; Ahsan Sadee Tanim; Nabila Nawal; Sharmin Akter (Journal of Information Systems Engineering and Business Intelligence, 2019)
Background: Tour recommendation and path planning are the most challenging jobs for tourists as they decide Points of Interest (POI).